Analisis Pengaruh Modal Kerja dan Biaya Operasional terhadap Laba Bersih Pada Perusahaan Makanan dan Minuman yang terdaftar di Bursa Efek Indonesia Periode 2022-2023 - Kertarajasa, Astro Yudha; Annisa, Mutiara Lusiana (LANCAH: Jurnal Inovasi dan Tren, 2024)
The objective of this study is to investigate the impact of working capital on net profit in food and beverage companies listed on the Indonesia Stock Exchange during the period 2022–2023. The research sample uses secondary data obtained from financial reports and annual reports of the companies. Untuk menentukan hubungan antara dependent variable (net profit) dan independent variables (working capital and operational costs), multiple linear regression analysis is used. The study's findings demonstrate that working capital significantly and negatively affects net profit. This demonstrates that net profit often declines as working capital rises and vice versa. All things considered, while having enough working capital is necessary for healthy operations, having too much of it might be a sign of ineffective management and lower net income. In order to preserve profitability and operational effectiveness, it is crucial for businesses to manage working capital as effectively as possible. On the other hand, net profit is positively and significantly impacted by operating costs. Because operational costs are a component of the expenses necessary to maintain a business's daily operations, they have a direct impact on a company's net profit. Net profit can rise when operational costs are managed effectively.